A study of top-quark mass measurement using the lepton energy distribution at the Large Hadron Collider - Seo Hyun An (European Physical Journal C: Particles and Fields, 2017)
Abstract We present a feasibility study of top-quark mass measurement using the lepton energy distribution in the top-quark decay $$t → bW → b\ell ν $$ t → b W → b ℓ ν at the LHC. The method used in this study requires only the lepton energy distribution at parton level. The analysis is performed in the lepton + jets final state by using fast simulation data corresponding to an integrated luminosity of approximately 20 fb $$^{-1}$$ - 1 at $$\sqrt{s}$$ s = 14 TeV. Events with exactly one lepton, at least four jets and two b jets are selected. The lepton energy distribution at parton level is obtained by applying the bin-by-bin unfolding technique. The study shows that the pole mass of the top quark can be measured with an uncertainty of the order of 1 GeV.